Language and Power: Positive Politeness as an Instrument of Indirect International Interest through Speech Act on United States’ and Ukraine’s President Calls Transcript. (Open Society Conference, 2023)
This paper is aim to discuss how the use of indirect speech act with positive politeness used by Trump as United States’ President and Zelensky as Ukraines’ President in their call conversation represent the power through language. We can see from the data that the conversation appear is related to the bilateral of United States and Ukraine’s political world and Ukraine’s national defense needed. The data, later on known as the causes of the request for Trumps impeachment in 2019, since the Americans though that Trumps used his status for power abused intend to sabotage Biden in United Stated Presidential election 2021. This research will focus on the utterances that use politeness strategy (Brown and Levinson, 1983), and discuss the meaning of speech act (Yule, 1996) and it’s relation to power dimension (Lavrentsova, 2010). This research applies descriptive qualitative method (Norman in Targadi, 2011), and the result of analysis shows that there is power use from Trump’s utterances in the call conversation, since United States helps Zelensky in Ukraine presidential election and for their prosperity, so Trump thinks that Zelensky needs to pay him back.